Mouth cancer – What is it to Me and You?. (2nd November 2020) - Lewis, Mike
Abstract : The single most important factor in improving mouth cancer survival rates is detecting a tumour before it has reached 2 cm in diameter and has not metastasized to the lymph nodes. Clear descriptions of the abnormalities are essential in referrals to aid the vetting process. The introduction of the lockdown has reduced the number of referrals, which will undoubtedly have a negative impact for patients.